2020
DOI: 10.7759/cureus.9849
|View full text |Cite
|
Sign up to set email alerts
|

Rare Case of Iatrogenic Myocardial Infarction Induced by Use of Pyridostigmine

Abstract: Myasthenia gravis is an auto-immune disease that results in muscle weakness caused by antibodies released against acetylcholine receptors at the presynaptic membrane. Treatment options include acetylcholinesterase medications that cause a wide range of side-effects by increasing the concentration of acetylcholine at the synaptic cleft. One peculiar side effect seen is the precipitation of myocardial infarction caused by an excess of acetylcholine especially among elderly females. We present an interesting case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Unlike acetylcholine, pyridostigmine is rarely reported as a trigger of CAS, and only four published cases of pyridostigmine-induced CAS have been reported to date (table 1). 1–4 One case is early-onset MG, age <50 years old, while others are late-onset MG. Gender preference in MG is bimodal; in other words, the prevalence of late-onset MG is higher in men and vice versa 10.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike acetylcholine, pyridostigmine is rarely reported as a trigger of CAS, and only four published cases of pyridostigmine-induced CAS have been reported to date (table 1). 1–4 One case is early-onset MG, age <50 years old, while others are late-onset MG. Gender preference in MG is bimodal; in other words, the prevalence of late-onset MG is higher in men and vice versa 10.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of publication regarding the rechallenge of pyridostigmine in patients with suspected pyridostigmine-induced CAS, the neurocardiologist team decided to discuss rechallenge with the patient in light of the following reasons: (1) pyridostigmine is the first-line and effective management for controlling MG symptoms; (2) the patient had ever received pyridostigmine with a dose of 120 mg/day without developing CAS. Moreover, all of the previous publications reported that CAS occurs at a higher dose of pyridostigmine (180–240 mg/day)2 4; (3) pyridostigmine-induced CAS is very rare and is the provisional, not definite, diagnosis and (4) CAS can spontaneously occur without a precipitator. Hence, we cannot confidently conclude that pyridostigmine is the cause of CAS before the rechallenge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is a multisystem disorder, cardiac involvement is seen in 16% of cases. Pericarditis, myocarditis, arrhythmia, and TC are worth mentioning myasthenia gravis-related cardiac complications [4][5][6][7][8][9][10]. Previous analysis shows a 15 times greater prevalence of secondary TC following MC than the general inpatient population and twice the odds of all-cause mortality in these patients [11].…”
Section: Introductionmentioning
confidence: 99%